Comparative Evaluation of Some Moxifloxacin Hydrochloride Tablet Brands Marketed in Nigeria Using Five Different Validated Analytical Methods (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Assay of pharmaceuticals is an important aspect of quality control. It is necessary to compare the bioequivalence of generic brands of the any drug to an innovator/comparator brand as this forms the basis for comparing their therapeutic equivalence.Objective: This study aimed to determine the most accurate method for the assay of moxifloxacin hydrochloride (MOX-HCl) tablet brands in Nigerian markets by using five different validated analytical methods and also verify their interchangeability.Material & Methods: This study involved three brands of MOX-HCl including the comparator brand, Moxiget®. The study involves both quality control tests including: weight uniformity, diameter, thickness, friability, hardness, disintegration, dissolution and content of active ingredient (assay) methods including: phosphate buffered UV-Vis spectrophotometric, UV spectrophotometric, kinetic spectrophotometric, colorimetry and utilization of oxidation-reduction reaction methods.Results: All the samples used for this study passed the quality control tests and thus were of standard quality and therefore pharmaceutically equivalent.Conclusion: This study therefore conclude that phosphate buffered UV-Vis spectrophotometry provide the most accurate method to assay Moxifloxacin tablet, colorimetry assay method can serve as a substitute to the preferred method for the moxifloxacin assay and the three samples assayed in this work are interchangeable with the comparator brand (Moxiget®).